Estimation of residual shear strength ratios of liquefied soil deposits from shear wave velocity - Ozener, Pelin (SPRINGER, 2012)
For sites susceptible to liquefaction induced lateral spreading during a probable earthquake, geotechnical engineers often need to know the undrained residual shear strength of the liquefied soil deposit to estimate lateral spreading displacements, and the forces acting on the piles from the liquefied soils in order to perform post liquefaction stability analyses. The most commonly used methods to estimate the undrained residual shear strength (Sur) of liquefied sand deposits are based on the correlations determined from liquefaction induced flow failures with SPT and CPT data. In this study, 44 lateral spread case histories are analyzed and a new relationship based on only lateral spread case histories is recommended, which estimates the residual shear strength ratio of the liquefiable soil layer from normalized shear wave velocity. The new proposed method is also utilized to estimate the residual lateral displacement of an example bridge problem in an area susceptible to lateral spreading in order to provide insight into how the proposed relationship can be used in geotechnical engineering practice.
Keywords: liquefaction; lateral spread; undrained residual shear strength; undrained residual shear strength ratio; shear wave velocity; LIQUEFACTION RESISTANCE; CASE-HISTORIES; EARTHQUAKE; SANDS; Engineering